Carbon quantum dots with intrinsic mitochondrial targeting ability for mitochondria-based theranostics. Issue 30 (24th July 2017) - Hua, Xian-Wu; Bao, Yan-Wen; Chen, Zhan; Wu, Fu-Gen
Abstract : A novel type of carbon quantum dot with intrinsic mitochondrial-targeting ability was prepared for mitochondria-targeted imaging and drug delivery. Abstract : We prepare for the first time a novel type of fluorescent carbon quantum dot (or carbon dot, CD) with intrinsic mitochondrial targeting ability by a one-step hydrothermal treatment of chitosan, ethylenediamine and mercaptosuccinic acid. The as-prepared CDs can realize mitochondrial imaging and mitochondria-targeted photodynamic cancer therapy without further modifications of other mitochondriotropic ligands (such as triphenylphosphine, TPP). Currently, many commercial mitochondrial probes suffer from the lack of modifiable groups, poor photostability, short tracking time, high cost and/or complicated staining procedures, which severely limit their applications in live-cell mitochondrial imaging. Compared to commercial mitochondrial probes such as MitoTrackers, our CDs exhibit remarkable features including ultra-simple and cost-effective synthesis, excellent photostability, facile storage, easy surface modification, wash-free and long-term imaging capability and negligible cytotoxicity. Besides, since mitochondria are susceptible to the reactive oxygen species generated during chemo-, photo- or radiotherapy, mitochondria-targeted cancer therapy has attracted much attention due to its satisfying anticancer efficiency. To test if the CDs can be used for mitochondria-targeted drug delivery, they were conjugated with a photosensitizer rose bengal (RB) and the resultant CDs–RB nanomissiles achieved efficient cellular uptake and mitochondrial targeting/accumulation, realizing mitochondria-targeted photodynamic therapy. We believe that the CD-based nanotheranostics holds great promise in various biomedical applications.